Spain Campaign Committee (circular) - Wilkinson, Ellen Cicely, 1891-1947; Gillies, William
C03-0017-001 Telegraphic Address: "LABREPCOM, SOWEST, LONDON." Telephone: VICTORIA 8016, 8017, 8018, 8019 THE LABOUR PARTY TRANSPORT HOUSE (South Block), SMITH SQUARE, LONDON, S.W.1. Secretary : J.S. MIDDLETON November 29, 1937 SPAIN CAMPAIGN COMMITTEE Dear Sir or Madam, A meeting of the Spain Campaign Committee will be held at the House of Commons on Wednesday, December 8, 1937 at 4.30 p.m. in a Committee Room upstairs reserved in the name of Mr. James Walker, M.P. We hope that you will make a special effort to attend. Yours faithfully, WILLIAM GILLIES ELLEN WILKINSON Joint Secretaries. 292C/946/3/17